Impact of adjuvant treatment modalities on survival outcomes in curatively resected pancreatic and periampullary adenocarcinoma - DANE, FAYSAL (AME PUBL CO, 2015)
Background: We examined the impact of adjuvant modalities on resected pancreatic and periampullary adenocarcinoma (PAC). Methods: A total of 563 patients who were curatively resected for PAC were retrospectively analyzed between 2003 and 2013. Results: Of 563 patients, 472 received adjuvant chemotherapy (CT) alone, chemoradiotherapy (CRT) alone, and chemoradiotherapy plus chemotherapy (CRT-CT) were analyzed. Of the 472 patients, 231 were given CRT-CT, 26 were given CRT, and 215 were given CT. The median recurrence-free survival (RFS) and overall survival (OS) were 12 and 19 months, respectively. When CT and CRT-CT groups were compared, there was no significant difference with respect to both RFS and OS, and also there was no difference in RFS and OS among CRT-CT, CT and CRT groups. To further investigate the impact of radiation on subgroups, patients were stratified according to lymph node status and resection margins. In node-positive patients, both RFS and OS were significantly longer in CRT-CT than CT. In contrast, there was no significant difference between groups when patients with node-negative disease or patients with or without positive surgical margins were considered. Conclusions: Addition of radiation to CT has a survival benefit in patients with node-positive disease following pancreatic resection.
Keywords: Pancreatic adenocarcinoma; adjuvant chemotherapy (adjuvant CT); adjuvant radiotherapy; SINGLE-INSTITUTION EXPERIENCE; RANDOMIZED CONTROLLED-TRIAL; SEER REGISTRY DATA; PHASE-III; RADIATION-THERAPY; FOLINIC ACID; CANCER; CHEMOTHERAPY; RADIOTHERAPY; GEMCITABINE